Host Immune Responses to Clostridioides difficile Infection and Potential Novel Therapeutic Approaches - Md Zahidul Alam; John E. Markantonis; John T. Fallon (Tropical Medicine and Infectious Disease, 2023)
Clostridioides difficile infection (CDI) is a leading nosocomial infection, posing a substantial public health challenge within the United States and globally. CDI typically occurs in hospitalized elderly patients who have been administered antibiotics; however, there has been a rise in the occurrence of CDI in the community among young adults who have not been exposed to antibiotics. C. difficile releases toxins, which damage large intestinal epithelium, leading to toxic megacolon, sepsis, and even death. Unfortunately, existing antibiotic therapies do not always prevent these consequences, with up to one-third of treated patients experiencing a recurrence of the infection. Host factors play a crucial role in the pathogenesis of CDI, and accumulating evidence shows that modulation of host immune responses may potentially alter the disease outcome. In this review, we provide an overview of our current knowledge regarding the role of innate and adaptive immune responses on CDI outcomes. Moreover, we present a summary of non-antibiotic microbiome-based therapies that can effectively influence host immune responses, along with immunization strategies that are intended to tackle both the treatment and prevention of CDI.